If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + 60 = 20m Reorder the terms: 60 + 8m = 20m Solving 60 + 8m = 20m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-20m' to each side of the equation. 60 + 8m + -20m = 20m + -20m Combine like terms: 8m + -20m = -12m 60 + -12m = 20m + -20m Combine like terms: 20m + -20m = 0 60 + -12m = 0 Add '-60' to each side of the equation. 60 + -60 + -12m = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -12m = 0 + -60 -12m = 0 + -60 Combine like terms: 0 + -60 = -60 -12m = -60 Divide each side by '-12'. m = 5 Simplifying m = 5
| 2/5a-42 | | 32r+4s=36r | | S+15=8 | | -2x-3+-3x=17 | | 20.8+2z=24 | | 7t=80+91 | | 17/12m=1/2m-11/4 | | 6x-4(4+2x)=-10(3x+10) | | -2x^2-4x+24=0 | | Y=45x+145 | | 2+11b= | | 10-2x=25 | | y=3y+8 | | 8-7x+2x=38 | | 50+3(x+6)=4x-5 | | 10-11(4+n)=8(7-7n) | | 4x-2x+6xy+21x+(-9)-9= | | 2x^2+9x-396=0 | | 1/2x-8=-5 | | -6(x+9)-9x=-3(x+2) | | 9x+9=5x+6 | | 3(6x+4)=6(-2x+5x+4) | | 6x+40-10x=100 | | (8a-5+1)=8-2(a-3) | | -7(n+7)=-4(1+3n) | | -5(2/7) | | 12.2x=69.6 | | 5x+2(-3x+13)=21 | | f=gmm/r^2 | | 18q^4r^3+3q^2r^2(6q^2r+4)-7qr= | | 17x-32=17x+15 | | (2/7)-5 |